Temblores documentados para el periodo colonial de Costa Rica - Peraldo Huertas, Giovanni (2011)
In the present article we transcribe a collection of documents of the Colonial period, that explicitly referred the occurrence of earthquakes in Costa Rica. They were partially included in Peraldo & Montero (1994). The documents rescue interesting details of the historical circumstances when the earthquakes occurred, such as the social environment, costumes, administrative affairs, among others.